Exploring Explainable AI (EXAI) – An Emerging Trend in Healthcare Sector - Pal, Chaitali; Yashvanth, M.; Rao, K. S. Srinivasa (Communications in Mathematics and Applications, 2024)
Industry 4.0 and COVID-19 drove businesses to adopt AI/ML amid VUCA, advancing toward Industry 5.0. Explainable AI (EXAI) fosters trust in healthcare’s digital shift, enhanced remote care, and chronic-disease management, ushering smarter decisions and better patient outcomes. The authors used snowball sampling via Google Forms, surveying hospitals, practitioners, vendors, and customers on healthcare technology adoption. Data were visualized and analyzed descriptively. Explainable AI (EXAI) shows significant promise in managing NCDs, with ML tools aiding better diagnosis and treatment. Once EXAI is integrated nationwide in healthcare, Indian businesses will pivot, analyzing new challenges, enabling data-driven solutions that enhance well being and innovation.